De novo KCNT1 mutations in early‐onset epileptic encephalopathy - Ohba, Chihiro; Kato, Mitsuhiro; Takahashi, Nobuya; Osaka, Hitoshi; Shiihara, Takashi; Tohyama, Jun; Nabatame, Shin; Azuma, Junji; Fujii, Yuji; Hara, Munetsugu; Tsurusawa, Reimi; Inoue, Takahito; et al. (Epilepsia (Copenhagen), 2015)
Summary KCNT1 mutations have been found in epilepsy of infancy with migrating focal seizures (EIMFS; also known as migrating partial seizures in infancy), autosomal dominant nocturnal frontal lobe epilepsy, and other types of early onset epileptic encephalopathies (EOEEs). We performed KCNT1‐targeted next‐generation sequencing (207 samples) and/or whole‐exome sequencing (229 samples) in a total of 362 patients with Ohtahara syndrome, West syndrome, EIMFS, or unclassified EOEEs. We identified nine heterozygous KCNT1 mutations in 11 patients: nine of 18 EIMFS cases (50%) in whom migrating foci were observed, one of 180 West syndrome cases (0.56%), and one of 66 unclassified EOEE cases (1.52%). KCNT1 mutations occurred de novo in 10 patients, and one was transmitted from the patient's mother who carried a somatic mosaic mutation. The mutations accumulated in transmembrane segment 5 (2/9, 22.2%) and regulators of K+ conductance domains (7/9, 77.8%). Five of nine mutations were recurrent. Onset ages ranged from the neonatal period (<1 month) in five patients (5/11, 45.5%) to 1–4 months in six patients (6/11, 54.5%). A generalized attenuation of background activity on electroencephalography was seen in six patients (6/11, 54.5%). Our study demonstrates that the phenotypic spectrum of de novo KCNT1 mutations is largely restricted to EIMFS.